FXYD8, a Novel Regulator of Renal Na+/K+-ATPase in the Euryhaline Teleost, Tetraodon nigroviridis - Wang, Pei-Jen; Yang, Wen-Kai; Lin, Chia-Hao; Hwang, Hau-Hsuan; Lee, Tsung-Han (Frontiers in Physiology, 2017)
FXYD proteins are important regulators of Na+/K+-ATPase (NKA) activity in mammals. As an inhabitant of estuaries, the pufferfish (Tetraodon nigroviridis) responds to ambient salinity changes with efficient osmoregulation, including alterations in branchial and renal NKA activities. Previous studies on teleostean FXYDs have mainly focused on the expression and potential functions of FXYD proteins in gills. The goal of the present study was to elucidate the potential role of FXYD8, a member of the fish FXYD protein family, in the modulation of NKA activity in the kidneys of this euryhaline pufferfish by using molecular, biochemical, and physiological approaches. The results demonstrate that T. nigroviridis FXYD8 (TnFXYD8) interacts with NKA in renal tubules. Meanwhile, the protein expression of renal TnFXYD8 was found to be significantly upregulated in hyperosmotic seawater-acclimated pufferfish. Moreover, overexpression of TnFXYD8 in Xenopus oocytes decreased NKA activity. Our results suggest the FXYD8 is able to modulate NKA activity through inhibitory effects upon salinity challenge. The present study further extends our understanding of the functions of FXYD proteins, the regulators of NKA, in vertebrates.